Host Plant Effects on Immune Response Across Development of a Specialist Caterpillar - Carper, Adrian L.; Enger, Micaela; Bowers, M. Deane (Frontiers in Ecology and Evolution, 2019)
Some herbivorous insects sequester chemicals from their host plants, which can serve as a defense against predators. However, sequestration can also be costly, impacting immunological responses important for other types of natural enemies, such as parasites and pathogens. These costs could also vary across herbivorous insect development, as both immune function and sequestration abilities change, although few studies have assessed variation in the cost of sequestration across life stages. The buckeye, Junonia coenia (Nymphalidae), is a specialist butterfly that sequesters iridoid glycosides from its host plants, including the introduced weed, Plantago lanceolata (Plantaginaceae). To determine the immunological costs of sequestration and how the immune response varies with host plant and across development, we reared caterpillars on a native host plant, Mimulus guttatus (Phrymaceae), which does not contain iridoid glycosides, and on P. lanceolata, which does. We assayed immune function across 3rd, 4th, and 5th instar caterpillars, estimating both hemocyte density and the ability of hemocytes to encapsulate foreign bodies by challenging the immune system with nylon filaments. For caterpillars reared on P. lanceolata, we then explored the relationships between iridoid glycoside sequestration and immune function across instars. We found that while hemocyte density tended to increase with instar regardless of host plant, caterpillars reared on P. lanceolata had lower encapsulation ability, and encapsulation decreased with increasing sequestration of iridoid glycosides, though patterns varied between instars and experimental periods. Interestingly, immune challenged caterpillars sequestered more iridoid glycosides than unchallenged caterpillars, suggesting that caterpillars responded to immune challenge by sequestering or retaining more iridoids, even though that may decrease their ability to encapsulate. These results suggest that sequestration can have important consequences for immune function across caterpillar development, and that the incorporation of novel hosts may affect defense against natural enemies.